Evaluasi Pelaksanaan Praktik Pembentukan Bahan Bengkel Fabrikasi Jurusan Pendidikan Teknik Mesin Fakultas Teknik Universitas Negeri Yogyakarta - Arif Marwanto; Aan Ardian; Suyanto Suyanto (Department of Mechanical Engineering Education, 2017)
The implementation of practice-work learning need to be evaluated periodically to determine wether the equipments and the learning methods are appropriate to the main purpose of learning, which is the establishment of learners' competency. The evaluation process in this research was carried out by adopting the CIPP evaluation methods. The research objects are lecturers and students participating in the Material Forming Practice course. Data were collected using documentation, observation and questionnaires and were analyzed using descriptive analysis. The results show that the implementation of Material Forming Practice course in the half semester of academic year 2016/2017 was very successful. Barriers faced by the lecturers were the lack of students' comprehension in flat pattern drawing, mathematical analysis skills, lack of motivation in reading jobsheet, and the lack of students' adaptation to the practice environment. Barriers faced by the students came from the lecturers, workpiece materials, low category workshop conditions, the shop equipments are in moderate category, whereas jobsheets and technicians are in the very low category. The condition of the equipments in terms of quantity is sufficient, but in terms of quality, many still needs repairs and renewals. The students' learning achiements in the midterm semester was the ability to finish 4 jobs with marks as follow: 53% were graded